KEBIJAKAN DIVIDEN DAN VOLATILITAS HARGA SAHAM (Studi Kasus pada Perusahaan Manufaktur di Indonesia) - Yuwana Sari, Rida; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2021)
The purpose of this research is to analyze the relationship between dividend policy and stock price volatility. This research is using stock price volatility as a dependent variable. As a proxy of dividend policy, dividend payout ratio and dividend yield are used as a independent variable. Then, firm size and earning volatility are added as a control variable. The population of this reseacrh is manufacturing companies listed on the Indonesia Stock Exchange and has never been delisted during the period 2014 – 2019. By purposive sampling method, 42 manufacturing companies were obtained as the sample of this research. The analytical method used in this reseacrh is multiple regression analysis. The result of this research indicate that dividend yield has a negative and significant effect on stock price volatility. Meanwhile, dividend payout ratio has insignificant effect on stock price volatility of manufacturing companies in Indonesia.